Leader-Member Exchange and Employee Performance: Mediating Roles of Work Engagement and Job Satisfaction - Jufrizen Jufrizen; Dita Sayidina Harahap; Hazmanan Khair (Universitas Hayam Wuruk Perbanas, 2023)
The purpose of this study is to investigate and evaluate the direct or indirect effects of leader-member exchange on work engagement and job satisfaction on employee performance. The study encompassed 215 employees who worked at the Office of the Regional Tax and Retribution Management Agency of Medan City, with 140 employees constituting the sample size. Questionnaires and interviews were employed in this study's data collection process. SmartPLS (Partial Least Square) 4.0 software is utilized for structural equation modeling in statistical analysis. The results of this study indicate that direct leader-member exchange, work engagement and job satisfaction have a significant effect on employee performance. Leader-member ex-change has a significant effect on performance through work engagement and employee job satisfaction at the Office of the Regional Tax and Retribution Management Agency of Medan City. This research provides information for the Office of the Regional Tax and Retribution Management Agency of Medan City and related parties to improve employee performance by increasing job satisfaction, and work engagement and improving existing leadership to provide employee comfort.